2005
DOI: 10.1111/j.1439-0310.2005.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Social Interactions and Breeding Success of the FrogRana latastei: A Field Study

Abstract: Interspecific reproductive interference can affect fitness-related breeding performance, thus influencing fitness and distribution of populations. Laboratory studies demonstrated the social interference of Rana dalmatina males on R. latastei breeding females: the presence of heterospecific males reduced the percentage of viable embryos in R. latastei eggs. Here, we tested if the negative effects of R. dalmatina males on R. latastei reproductive success occur in field conditions. We compared the percentage of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 37 publications
2
53
0
1
Order By: Relevance
“…Laboratory results from standardized environments can not always be extended to the field, where the environment is more variable and generally different from that of the laboratory (MCKENZIE 1996 ande.g. DE FOUNTAIN andHOPKIN 2004;STOOPS 2005;FICETOLA and BERNARDI 2005). Measures from laboratory studies on a particular trait may prevent any extrapolation to fitness in natural environment, which is not, in fact, very surprising.…”
Section: Comparison With Laboratory Experimentsmentioning
confidence: 99%
“…Laboratory results from standardized environments can not always be extended to the field, where the environment is more variable and generally different from that of the laboratory (MCKENZIE 1996 ande.g. DE FOUNTAIN andHOPKIN 2004;STOOPS 2005;FICETOLA and BERNARDI 2005). Measures from laboratory studies on a particular trait may prevent any extrapolation to fitness in natural environment, which is not, in fact, very surprising.…”
Section: Comparison With Laboratory Experimentsmentioning
confidence: 99%
“…Similar to resource competition, reproductive interference is density‐dependent (Hettyey and Pearman 2003) and in most cases asymmetric (Fujimoto et al 1996). It can affect population dynamics, abundance, habitat choice and distribution of species (Kuno 1992, Ficetola and De Bernardi 2005). It has been suggested that demographic displacement of one species caused by reproductive interference (sexual exclusion) is even more likely than competitive exclusion (Ribeiro and Spielman 1986, Kuno 1992, Hochkirch et al in press).…”
mentioning
confidence: 99%
“…repatriations best performed in permanent ponds where water permanence during all the breeding period allows the completion of the reproductive cycle. The positive effect on repatriation outcome of pond's shore incline might be related to the preference of the species for deep and permanent wetlands (Ficetola and De Bernardi, 2005b): shore incline may therefore be an effective predictor for depth (and also better than the actual measure of depth) since water levels in our study area are subjected to unpredictable fluctuations due to industrial and agricultural employ of water, as well as rainfall.…”
Section: Discussionmentioning
confidence: 99%